Case report: Continuous infusions of ceftazidime-avibactam and aztreonam in combination through elastomeric infusors for 12 weeks for the treatment of bone and joint infections due to metallo-β-lactamase producing Enterobacterales - Merad, Yanis; Conrad, Anne; Brosset, Sophie; Schmidt, Axel; Hanriat, Camille; Lustig, Sebastien; Laurent, Frederic; Kolenda, Camille; Roussel-Gaillard, Tiphaine; Batailler, Cecile; Ferry, Tristan; , Lyon BJI Study group (Frontiers in Medicine, 2023)
Among carbapenem-resistant Enterobacterales, metallo-beta-lactamase producing strains represent a growing therapeutic challenge. While the association of aztreonam and ceftazidime-avibactam has been investigated in recent years for the treatment of infections involving these strains, little to no clinical data support the use of this association for the treatment of bone and joint infections. We report two cases of complex bone and joint infections involving metallo-beta-lactamase-producing Enterobacterales, successfully treated at our referral center with aztreonam and ceftazidime-avibactam for 12 weeks in continuous infusions through elastomeric infusors.